Multi-criterion optimization of urban public electric transport routes - Zakharov, Denys; Palant, Oleksii; Proskurnin, Oleg; Belokon, Karina; Krasnoshtan, Olexander; Tsymbal, Serhii (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the public transport route network. The task addressed is to choose optimal transport routes. Existing scientific research in this field is mainly aimed at increasing its reliability and reducing economic risks. The social and environmental aspects are considered separately, not in connection with technical and economic issues. The study proposes a comprehensive approach to solving the task of urban transport operation. To solve the problem of multi-criteria optimization of the transport network, the use of the hierarchy analysis method (HAM), which is based on expert assessments, has been proposed. A hierarchical structure of the route selection problem was constructed. Three optimization criteria were determined, as well as ten factors influencing the selected criteria. A comprehensive approach to choosing urban electric transport routes could make it possible, with minimal capital investments and operating costs, to promote the normal functioning of cities. This is especially relevant for Ukraine, which in the post-war period, due to demographic changes and changes in local infrastructure, will face the need to radically revise the operation mode of public transport. The advantage of HAM over other expert methods is the complex hierarchical structure of cause-and-effect relationships between the choice of the optimum and alternative options, as well as the presence of a mechanism for internal control over the consistency of expert judgments. The procedure for using HAM has been demonstrated using an example of optimizing transport communication between two districts in the city of Kharkiv (Ukraine). The existing tram route was considered, as well as alternative options. The option consisting of one tram and one trolleybus route was chosen as optimal according to technical, economic, social, and environmental criteria